Complementary and alternative medicine: Knowledge and attitude of medical students of the uniKL-RCMP, Perak, Malaysia - Mainul, Haque; A. T. M. Emdadul, Haque; Farrah Hanum, Abdul Kadir (Research Journal of Pharmacy and Technology, 2015)
Introduction